Modelo de cuantificación del impacto de la falsificación de productos en el valor de la empresa - Katia Lorena Rodríguez Morales (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2014)
– Due to the difference in legislation and controls, lately is when counterfeiters have found greater opportunities to counterfeit and create a parallel economy that causes social damages, and affects companies that own original brands, making it necessary to quantify this damage. We developed a financial model on which to assess the change in value of a company harmed due to counterfeiting, describing how it affects negatively the quantity demanded of the originals, and the firm's expenses while seeking to preserve its value.
Keywords: M19; 330; Counterfeit; Brand valuation; Discounted cash flow